Residual post-pandemic ICT literacy in higher education: The case of foreign language teachers and students in Japan - Campos Tejero, O. Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The COVID-19 pandemic forced higher educational institutions to an emergent transition to online education, which required that teachers and students were ICT literate enough to continue with their curricula. As most universities in Japan have already transitioned back to face-to-face lessons, this study aimed to analyze the process of acquisition and use of ICT knowledge in a pre, mid and post-pandemic scenario. Findings showed a drastic gap of ICT literacy between teachers and students. However, results suggest that the acquired ICT knowledge remained and is currently being used in a face-to-face or hybrid environment.